Fish pellet development utilizing BSF Maggot by-product organic fertilizer for economic growth - Andrew Setiawan Rusdianto; Achmad Shorfi Aldini; Fitri Wulandari; Dian Nur Fauziayah; Larissa Nathania Marella; Anika Ratnawati; Nur Hayati; Ahmad Nurul Azis; Zuhal Febrian; Ferdinand Simanjuntak; Ahmad Rafid Zuhdi (University of Merdeka Malang, 2023)
The village of Sukamakmur has the potential for freshwater fishery resources through catfish farming. Black Soldier Fly larvae (BSFl) cultivated by the Farmer Group Tirto Bakti II can solve farmers’ dependence on factory-made feeds, alongside the underutilization due to a lack of technological input in processing by-products. This service activity aims to develop the application of fish feed technology using BSFl to meet the nutritional needs of fish, increase the market value of fish pellet products, and establish partnerships with catfish farmers and community groups in the village. The development activities involve outreach efforts to explain the production process from the materials used to the manufacturing process. The product development results indicate that the material formulation used in making fish pellets consists of a successive mixture of BSFl: bran: fish meal: tapioca flour in a ratio of 4:2:1:1 with a floating capability of approximately 5-7 minutes. Based on the service activities that have been carried out, this service can encourage continued production in the Tirto Bakti II Farmer Group as a new initiative in managing BSFl, with the impact of improving the economy through new activities and marketing.